ナンタイヨウインドヨウク デ サイシュウ サレタ NORPAC ネット ヒョウホン ニ オケル ドウブツ プランクトン シツジュウリョウ ノ サイヒョウカ - 鵜飼, 由紀子; ウカイ, ユキコ; 高橋, 邦夫; タカハシ, クニオ; 福地, 光男; フクチ, ミツオ; 谷村, 篤; タニムラ, アツシ; Ukai, Yukiko; Takahashi, Kunio T.; Fukuchi, Mitsuo; Tanimura, Atsushi (2014)
P(論文) 日本南極地域観測隊(JARE)による長期モニタリング観測の一環として40 年以上に渡り継続して実施している,NORPAC ネットによる動物プランクトン標本の湿重量値の再評価を行った.これまで報告されてきた湿重量値は植物プランクトンの混入による影響が問題視されてきたため,動物プランクトンのみを計測する標本精査を実施した.動物相をターゲットにした目合い330 μm で採集された動物プランクトン標本においては,総湿重量の26.7 % が混入した植物プランクトンであり,これまでの報告値は約3 割程度の過大評価であったことが明らかとなった.また330 μm と100 μm の両ネット地間での湿重量を比較すると,10 mm 以上の動物プランクトンでは有意な差が見られず,一方で10 mm 未満の動物プランクトンでは,100 μm により採集された標本が330 μm で採集されたものの約2 倍であることが明らかとなった.本研究で実施した標本の精査方法により,植物プランクトンの混入による影響の除外,例外的に高い湿重量値をもたらした大型動物プランクトンの原因種の特定,1 mm 以下の小型動物プランクトンの生物量の評価が可能となった.植物プランクトンの混在する標本間において,混入割合に大きなバラつきが生じていることから,将来的には全標本を精査し,再度湿重量を測りなおす必要があると考えられた. The Japanese Antarctic Research Expedition (JARE) has been conducting routine observations of zooplankton in the Indian Ocean sector of the Southern Ocean with standard NORPAC nets (mesh size: 330 μm and 100 μm) every austral summer since the 1972/73 season (JARE-14). We used a new processing method to measure the wet weight of the zooplankton only because the effect of the inclusion of phytoplankton on the wet weight has been problem in previous studies. The repeated-measurement made in this study show that 26.7 % of the total wet weight of the samples that were collected with 330 μm (targeting zooplankton) was attributable to phytoplankton. We have thus demonstrated that previous reports have overestimated the wet weight of zooplankton by approximately 30 %. Furthermore, when we compared the wet weights caught with the 330 μm and 100 μm nets, they did not differ significantly for zooplankton greater than 10 mm, whereas the wet weights of small sized zooplankton less than 10 mm caught with 100 μm nets were approximately two-fold greater than those caught with 330 μm nets. departmental bulletin paper